Analysis of the Protective Efficacy of Approved COVID-19 Vaccines Against Various Mutants - Li, Chaonan; Guo, Yikai; Fang, Zhongbiao; Zhang, Haiyan; Zhang, Yanjun; Chen, Keda (Frontiers in Immunology, 2022)
The outbreak of COVID-19 (caused by SARS-CoV-2) has posed a significant threat to global public health security because of its high pathogenicity and infectivity. To date, the pathogenic mechanism of this novel coronavirus (SARS-CoV-2) is still unclear, and there is no effective treatment. As one of the most effective strategies to prevent viral infection, vaccines have become a research hotspot. Based on the current understanding of SARS-CoV-2, the research and development of its vaccines cover almost all forms of current vaccine research, including inactivated vaccines, recombinant protein vaccines, viral vector vaccines, and nucleic acid vaccines. Moreover, with the spread of the new mutant virus, it is necessary to evaluate the protection rate of previous administered vaccines. This article reviews the candidate targets, vaccine types, research and development status, progress of SARS-CoV-2 vaccines, and the effectiveness of neutralizing antibodies against SARS-CoV-2 mutants (B.1.1.7, B.1.351, P.1, B.1.617.2, and B.1.1.529) induced by these vaccines, to provide a reference for follow-up research and prevention.